Delayed Anterior Cruciate Ligament Reconstruction in Young Patients With Previous Anterior Tibial Spine Fractures. (August 2016) - Mitchell, Justin J.; Mayo, Meredith H.; Axibal, Derek P.; Kasch, Anthony R.; Fader, Ryan R.; Chadayammuri, Vivek; Terhune, E. Bailey; Georgopoulos, Gaia; Rhodes, Jason T.; Vidal, Armando F.
Background: Avulsion fractures of the anterior tibial spine in young athletes are injuries similar to anterior cruciate ligament (ACL) injuries in adults. Sparse data exist on the association between anterior tibial spine fractures (ATSFs) and later ligamentous laxity or injuries leading to ACL reconstruction. Purpose: To better delineate the incidence of delayed instability or ACL ruptures requiring delayed ACL reconstruction in young patients with prior fractures of the tibial eminence. Study Design: Case series; Level of evidence, 4. Methods: We identified 101 patients between January 1993 and January 2012 who sustained an ATSF and who met inclusion criteria for this study. All patients had been followed for at least 2 years after the initial injury and were included for analysis after completion of a questionnaire via direct contact, mail, and/or telephone. If patients underwent further surgical intervention and/or underwent later ACL reconstruction, clinical records and operative reports pertaining to these secondary interventions were obtained and reviewed. Differences between categorical variables were assessed using the Fisher exact test. The association between time to revision ACL surgery and fracture type was assessed by Kaplan-Meier plots. The association between need for revision ACL surgery and age, sex, and mechanism of surgery was assessed using logistic regression. Results: Nineteen percent of all patients evaluated underwent delayed ACL reconstruction after a previous tibial spine fracture on the ipsilateral side. While there were a higher proportion of ACL reconstructions in type II fractures, there was not a statistically significant difference in the number of patients within each fracture group who went on to undergo later surgery ( P = .29). Further, there was not a significant association between fracture type, sex, or mechanism of injury as it related to the progression to later ACL reconstruction. However, there was a significant association between age at the time of injury and progression to later ACL reconstruction ( P = .02). For every year increase in age at the time of injury, the odds of going on to undergo delayed ACL reconstruction were greater by a factor of 1.3 (95% CI, 1.1-1.6). Conclusion: Although an ATSF is a relatively rare injury, our cohort of patients suggests that a subset of young patients with all types of tibial spine fractures will require later ACL reconstruction. There is a need to counsel patients that a delayed ACL rupture is a potential risk after an ATSF, especially as children approach skeletal maturity. Further patient follow-up and prospective studies are required.